Code Switching in the English Learning Process for Nursing Students - Sulistiyaningsih, Riski (Journal of Education, Language Innovation, and Applied Linguistics, 2025)
This research aims to explain the learning process for English courses in the Nursing Science department which uses code switching. The code switching used is from English to Indonesian and vice versa. This research uses a qualitative descriptive method. The object of this research is the type of speech used during the learning process for English courses in the Nursing Science department and the factors which cause the use of the code-switching during learning activities in the classroom. Data was taken using observation and interviews. The research results show that the use of code switching that occurs during the English learning process is situational code switching, namely internal and external code switching. Factors that influence the occurrence of code switching are (1) the difficulty of finding equivalent words, (2) the habit of students, (3) Lack of understanding of certain vocabulary in the scientific field (nursing science) in English, (4) the topic of conversation, ( 5) factors to obey the rules, and (6) factors to make easier in delivering the lesson. By looking at these conditions, the use of code switching in the English learning process can be used as long as it is used to fulfill an academic function, namely improving students' English competence.